Mediation, by Saccharomyces cerevisiae translocation signals, of beta-lactamase transport through the Escherichia coli inner membrane and sensitive method for detection of signal sequences. - Roggenkamp, R (1986)
Signal sequences of Saccharomyces cerevisiae invertase and alpha-factor pheromone were tested for the ability to mediate protein transport through the inner membrane of Escherichia coli by fusion to bacterial beta-lactamase lacking the signal sequence (blaS0). Both types of transformants exhibited ampicillin resistance in accordance with the transport of the fused protein to the periplasmic compartment. This compartment contained most of the beta-lactamase activity present in the cell. Therefore, the tested yeast signal sequences, which conferred translocation of their proteins across the membrane of the endoplasmic reticulum in S. cerevisiae, can provide the same function in E. coli. The screening for ampicillin resistance among blaS0 fusions provides a convenient method for the isolation of functional yeast and possibly higher eucaryotic signal sequences.